EFEKTIVITAS PIJAT BAYI DALAM MENINGKATKAN ISTIRAHAT (TIDUR) BAYI USIA 4-6 BULAN DI BPM NY. SISWATI HARIONO, AMD.KEB DESA KEJAPANAN KEC. GEMPOL KAB. PASURUAN - Yulianti, Indra; Rizqi Maulidiah, Hani (JURNAL KEPERAWATAN SEHAT, 2015)
Sleep was a requirement which must be fulfilled especially at growth phase because growth and development happened during sleep. Sleep disorder was a problem that causes bad effect to infant’s growth and development. One of medicinal therapy for use increase rest (sleep) with baby massage. Research of purpose was to prove of baby massage effective within increase rest (sleep) of baby at Siswati Hariono’s BPM Pasuruan regency. Method of research to using Quasy Eksperimental with program of one group pre test -post test design. Population in this research was all of baby in age 4-6 month. Sample in this research was a part of baby in age 4-6 month at Siswati Hariono’s BPM Pasuruan regency fill the criteria of inclusive. Technical of removal sample was Purposive Sampling with 25 respondent. Instrument to used in this research i s SPO of baby massage and a piece of observation rest (sleep). Result of experiment statistics with expriment Wilcoxon Signed Rank use SPSS for Windows is signifikan that is ρ = 0,000 with α = 0,05. Knot of this research is baby massage is efective within increase rest (sleep) on babies at Siswati Hariono’s BPM Pasuruan regency. According to this result, expectly of baby massage can be applied by power of health and a mother have babies to increase rest (sleep) without cure farmacologist that perpetual.Keyword: Baby Massage, rest (sleep), 4-6 month age